The Combined Role of Immunotherapy and Radiotherapy in Muscle-Invasive Bladder Cancer: A Systematic Review - Aristya Ika Wardani (Pusat riset dan Inovasi Nasional, 2026)
Muscle-invasive bladder cancer (MIBC) is an aggressive malignancy associated with high morbidity, reduced survival, and impaired quality of life. Radiotherapy (RT) has been widely used as a bladder-preserving strategy, particularly for patients unsuitable for surgery or systemic chemotherapy. RT may also enhance tumor immunogenicity through programmed death-ligand 1 (PD-L1) upregulation, providing a rationale for combination therapy with immunotherapy. This study aimed to evaluate the effectiveness of combining immunotherapy and radiotherapy in MIBC treatment. A systematic review was conducted following PRISMA 2020 guidelines using the PICO framework. Literature searches were performed in PubMed, Embase, Cochrane, ClinicalTrials.gov, Web of Science, and Scopus databases for studies published between 2016 and 2025. Risk of bias was assessed using the Cochrane Risk of Bias Tool and ROBINS-I. Of 105 identified studies, five met the inclusion criteria and were included in the final analysis. Only one Phase II randomized controlled trial demonstrated low risk of bias in randomization and allocation concealment. ROBINS-I assessment indicated moderate to serious risk in confounding and participant selection domains. Clinical findings showed promising outcomes, with complete response rates ranging from 35%–50% and partial response rates from 25%–40%. Median overall survival ranged from 24–30 months, with favorable disease-free and progression-free survival outcomes. Combined immunotherapy and radiotherapy demonstrate potential to improve survival and disease control in MIBC; however, further rigorous clinical studies are needed to optimize patient-centered treatment strategies.